搶救過去的記憶 : 口述歷史應用在圖書館之探析 Save the Memory：The study of oral history in the library - Sheue-fang Song; Shih-ying Shiu (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
口述歷史是透過人們的回憶所建構起來的歷史。近年來口述歷史的應用更為昔遍，不僅許多學科領域及民間歷史團體紛紛運用口述歷史方法豐富自身歷史的維度，更大的意義在於口述歷史為長期被忽略的階層及社群提供發言的位置。本文即以口述歷史建構史料的角度出發，探討圖書館史與口述歷史的關係，分析美國與台灣的圖書館界從事口述歷史的情況，目的在喚起圖書館界同仁搶救圖書館歷史的危機意識，免於日後這些活歷史渺茫難覓的遺憾。 Oral history is a historical approach that is based on the use of personal reminiscences.Oral library history is to writing library history that relies in large part on interviews with elderly librarians or professors who provide retrospective data on the library events,attitudes, and activities of their life-in effect a transfer of the interview. This article isstudy of the library oral history in Taiwan and America. The purpose is wished to save some librarians memory which can structure the library history.